2015
DOI: 10.1002/srin.201500310
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Segregation of High‐Manganese Steels from 2‐D Phase‐Field Simulations, 1‐D Analytical Theories, and Solidification Experiments

Abstract: This paper presents a study comparing the microsegregation from 2-D phase-field simulations with those predicted by 1-D analytical theories and with the ones obtained from experiments. It focuses mainly on the solidification of an Fe-Mn binary alloy with high manganese content (23 wt%), which is comparable to the manganese content of highmanganese steel (HMnS) grades. The main motivation for this study comes from the strong influence of microsegregation on the local mechanical properties of these steels at roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Senk et al investigated the microstructure and micro segregation behavior of the Fe–Mn–Si–Al high manganese steel using the phase filed model and the simulation results were in good agreement with that of the experiment. Alves et al revealed that the phase field model was a great method to investigate the micro segregation of Mn with high Mn content (≈23 wt%).…”
Section: Introductionmentioning
confidence: 99%
“…Senk et al investigated the microstructure and micro segregation behavior of the Fe–Mn–Si–Al high manganese steel using the phase filed model and the simulation results were in good agreement with that of the experiment. Alves et al revealed that the phase field model was a great method to investigate the micro segregation of Mn with high Mn content (≈23 wt%).…”
Section: Introductionmentioning
confidence: 99%
“…Performed calculations of the phase composition in the system Fe- (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)Mn-(10-12.0)Al-1-2 C (wt%) indicate that in the considered range of concentrations, the appearance of undesirable phases during hardening is possible. Therefore, for such steels, it is crucial to ensure a stable composition and favorable solidification conditions to obtain a uniform structure: the cooling rate should be high but not cause cracks in the surface area.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, a limited number of publications are devoted to the melting and refining of high‐manganese steels to remove harmful admixtures, [ 20,21 ] as well as research focused on casting and solidification. [ 22,23 ] Furthermore, there is a scarcity of studies examining the effect of slag on the final composition of these steels. [ 24 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Micro-segregation in high Mn steels can have a significant effect on the mechanical properties at ambient temperature. [17][18][19] Compared to fundamental aspects and the properties under application conditions, the behavior of high and medium Mn steels during production and processing has not found so much attention. The behavior during cold rolling has been investigated by Ofei et al [20] The strain rate effect on the mechanical properties is important to adjust forming processes to the specific material and it is furthermore important for the crash performance in automotive applications.…”
mentioning
confidence: 99%